Calpain inhibition as a possible new therapeutic target in multiple sclerosis - Amena W. Smith; Swapan K. Ray; Arabinda Das; Kenkichi Nozaki; Baerbel Rohrer; Naren L. Banik (AIMS Molecular Science, 2017)
Multiple sclerosis (MS), the most common chronic autoimmune inflammatory disease of the central nervous system (CNS), is characterized by demyelination and neurodegeneration. In particular, neurodegeneration is a major factor in disease progression with neuronal death and irreversible axonal damage leading to disability. MS is manageable with current therapies that are directed towards immunomodulation but there are no available therapies for neuroprotection. The complex pathophysiology and heterogeneity of MS indicate that therapeutic agents should be directed to both the inflammatory and neurodegenerative arms of the disease. Activity of the Ca2+ activated protease calpain has been previously implicated in progression of MS and its primary animal model, experimental autoimmune encephalomyelitis (EAE). The effects of calpain inhibitors in EAE involve downregulation of Th1/Th17 inflammatory responses and promotion of regulatory T cells, overall leading to decreased inflammatory cell infiltration in CNS tissues. Furthermore, analysis of brains, spinal cords and optic nerves from EAE animals revealed decreases in axon degeneration, motor neuron and retinal ganglion cell death. This resulted in improved severity of paralysis and preservation of visual function. Taken together, the studies presented in this brief review suggest that use of calpain inhibitors in combination with an immunomodulatory agent may be a potential therapeutic strategy for MS and optic neuritis.